Prevalence of protective antibody levels against hepatitis B infection among healthcare workers in a tertiary care hospital in India - Thanikachalam, Ramesh; Elangovan, Sathyan; Grace, Jercy (Asian Journal of Medical Sciences, 2023)
Background: Hepatitis B virus (HBV) infection affects more than 2 billion individuals globally HBV. The chance of dying from liver cirrhosis, acute fulminant liver disease, or hepatocellular carcinoma (HCC) is present in 240 million of these chronic HBV carriers (HCC). Aims and Objectives: This study aims to assess the anti-HBs antibody titer level against various levels of healthcare workers (HCWs) and to assess the need for booster dose hepatitis B vaccination. Materials and Methods: This study was conducted at Melmaruvathur Adhiparasakthi Institute of Medical Sciences and Research, Melmaruvathur, Tamil Nadu, India, from July 2022 to December 2022. A total of 218 HCWs were divided into two groups: Group A (vaccinated ≥5 years ago) and Group B (vaccinated in past 5 years). The serum from 2 mL blood was separated and tested for anti HBs antibody titer by electrochemiluminescense immunoassay method. Results: The mean and standard deviation values of Anti-HBsAg titer between Group A and Group B was not statistically significant (P=0.08467). Conclusion: Our study demonstrates that people who have had vaccinations are unsure of whether they are responders or non-responders, and to determine this, they must have had their titer evaluated only 1–2 months after receiving their third dosage of hepatitis B vaccine. As a result, they still run the risk of contracting hepatitis B and strongly need a booster dose of the hepatitis B vaccine.